“Going to town”: Large-scale norming and statistical analysis of 870 American English idioms - Bulkes, Nyssa Z.; Tanner, Darren (Behavior Research Methods, 2017)
An idiom is classically defined as a formulaic sequence whose meaning is comprised of more than the sum of its parts. For this reason, idioms pose a unique problem for models of sentence processing, as researchers must take into account how idioms vary and along what dimensions, as these factors can modulate the ease with which an idiomatic interpretation can be activated. In order to help ensure external validity and comparability across studies, idiom research benefits from the availability of publicly available resources reporting ratings from a large number of native speakers. Resources such as the one outlined in the current paper facilitate opportunities for consensus across studies on idiom processing and help to further our goals as a research community. To this end, descriptive norms were obtained for 870 American English idioms from 2,100 participants along five dimensions: familiarity, meaningfulness, literal plausibility, global decomposability, and predictability. Idiom familiarity and meaningfulness strongly correlated with one another, whereas familiarity and meaningfulness were positively correlated with both global decomposability and predictability. Correlations with previous norming studies are also discussed.